(15b-9)-7(2b+3)=-5

Simple and best practice solution for (15b-9)-7(2b+3)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (15b-9)-7(2b+3)=-5 equation:


Simplifying
(15b + -9) + -7(2b + 3) = -5

Reorder the terms:
(-9 + 15b) + -7(2b + 3) = -5

Remove parenthesis around (-9 + 15b)
-9 + 15b + -7(2b + 3) = -5

Reorder the terms:
-9 + 15b + -7(3 + 2b) = -5
-9 + 15b + (3 * -7 + 2b * -7) = -5
-9 + 15b + (-21 + -14b) = -5

Reorder the terms:
-9 + -21 + 15b + -14b = -5

Combine like terms: -9 + -21 = -30
-30 + 15b + -14b = -5

Combine like terms: 15b + -14b = 1b
-30 + 1b = -5

Solving
-30 + 1b = -5

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '30' to each side of the equation.
-30 + 30 + 1b = -5 + 30

Combine like terms: -30 + 30 = 0
0 + 1b = -5 + 30
1b = -5 + 30

Combine like terms: -5 + 30 = 25
1b = 25

Divide each side by '1'.
b = 25

Simplifying
b = 25

See similar equations:

| 2(x+y)+3x+2y= | | 9x+4x+4+9=5x+3+7x | | 6p+9=18+5p | | -2=-4x^2+12x+14 | | 7x=6x+2 | | 14=-4x^2+12x+14 | | 0.20(18)+0.05x=0.10(6+x) | | 28=x^2+9x+18 | | 4=x^2+9x+18 | | 3x+(-3y)-(4x)+y= | | 172-4x=23x+16 | | 2x^6w^4*2w^3*4x= | | 6=x^2-7x+12 | | 2=x^2-7x+12 | | 2x^2-x=120 | | 1.25x+0.125x=0.875+x | | 3x^2+9x=54 | | -16x^2+220x=0 | | 7+2x*5=x*6+11 | | -8x^3-20x^2=8x | | (5x+4)(3x-3)=0 | | x-8=4x | | 9x^2=51x-60 | | 6(t-5)+8t=7(2t+4)-11 | | 5t+2+4t-8t=5+5 | | 4(x-3)=-(x+7) | | (x-5)(x+3)(x+4)=0 | | x-(x+1)=12-(3x-2) | | y=x^2-x-23 | | 4(9v+2)=6(1+6v)-10 | | 2x=x+65 | | -2(c-d)+(c-3d)-5(c-d)= |

Equations solver categories